Deep Ultraviolet Light-Emitting Diode Light Therapy for Fusobacterium nucleatum - Soichiro Fukuda (Microorganisms, 2021)
Background: Fusobacterium nucleatum, which is associated with periodontitis and gingivitis, has been detected in colorectal cancer (CRC). Methods: We evaluated the bactericidal effect of deep ultraviolet (DUV) light-emitting diode (LED) light therapy on F. nucleatum both qualitatively and quantitatively. Two DUV-LEDs with peak wavelengths of 265 and 280-nm were used. DNA damage to F. nucleatum was evaluated by the production of cyclobutane pyrimidine dimers (CPD) and pyrimidine (6–4) pyrimidone photoproducts (6–4PP). Results: DUV-LEDs showed a bactericidal effect on F. nucleatum. No colony growth was observed after 3 min of either 265 nm or 280 nm DUV-LED irradiation. The survival rates of F. nucleatum under 265 nm DUV-LED light irradiation dropped to 0.0014% for 10 s and to 0% for 20 s irradiation. Similarly, the survival rate of F. nucleatum under 280 nm DUV-LED light irradiation dropped to 0.00044% for 10 s and 0% for 20 s irradiation. The irradiance at the distance of 35 mm from the DUV-LED was 0.265 mW/cm2 for the 265 nm LED and 0.415 mW/cm2 for the 280 nm LED. Thus, the radiant energy for lethality was 5.3 mJ/cm2 for the 265 nm LED and 8.3 mJ/cm2 for the 280 nm LED. Amounts of CPD and 6–4PP in F. nucleatum irradiated with 265 nm DUV-LED light were 6.548 ng/µg and 1.333 ng/µg, respectively. Conclusions: DUV-LED light exerted a bactericidal effect on F. nucleatum by causing the formation of pyrimidine dimers indicative of DNA damage. Thus, DUV-LED light therapy may have the potential to prevent CRC.